An investigation into the effect of knowledge management on employee retention in the telecom sector - Nurul Mohammad Zayed; Friday Ogbu Edeh; Khan Mohammad Anwarul Islam; Vitalii Nitsenko; Tetiana Dubovyk; Hanna Doroshuk (Administrative Sciences, 2022)
Employees in the telecom sector are knowledge workers and, thus, managers, HR professionals, and policymakers in the industry need to retain them through knowledge management policies. It is against this premise that this study investigated the effect of knowledge management on employee retention in the telecom sector. Research design employed in this study is a cross-sectional survey with an accessible population of thirty telecom companies in the southeastern region of Nigeria using a simple random sampling technique. The sample size was determined with the Krejcie and Morgan sample size determination table. A questionnaire was used as an instrument for data collection. Respondents' profiles were analysed with frequency distribution while the formulated hypotheses were analysed with linear regression. The study found that knowledge management dimensions have a significant effect on the measures of employee retention. The study concludes that knowledge management measured in terms of knowledge acquisition, knowledge storage, and knowledge sharing predicted employee retention that is measured by supervisor support, coworkers support, and flexible working arrangements. One of the implications of this study is that managers of telecom companies should liaise with their board of directors to make funds available that would be used to train employees to acquire relevant knowledge that is needed in the telecom industry.
Keywords: 350; coworker support; employee retention; flexible working arrangements; knowledge management; supervisor support; telecom